The effectiveness of using educational platforms in teaching mathematics and its impact on achievement and the trend towards it. (Journal of the College of Basic Education, 2023)
Summary of the research:The research aimed to investigate the effectiveness of using educational platforms in teaching mathematics on the achievement of students of the College of Basic Education in the mathematics course and their attitudes towards it compared to traditional methods that depend on recitation. The research sample consisted of (180) male and female students, who were randomly assigned to Two groups, an experimental group consisting of (90) male and female students, taught mathematics by educational platforms within an interactive educational environment that employs web technology and combines the features of electronic content management systems with social networks, where lessons and objectives were published, duties were determined, roles were distributed, and students were divided into groups. Working groups that helped them exchange ideas and opinions between teachers and students, share content, apply educational activities, communicate with teachers through multiple communication techniques, and the possibility of conducting training electronic tests, and a control group consisting of (90) male and female students who were taught the same unit using traditional methods (the usual method or the method of explanation). or lecture) in the same classrooms. In order to achieve the objectives of the research, an achievement test was used in the teaching unit and a trend scale after studying its validity, reliability, and the validity of its application in the Iraqi environment. The results of the pre-application analysis revealed the equivalence of the two research groups in both the achievement test and the attitudes scale. After analyzing the students’ scores in the achievement test and the trends scale using the t-test, the results showed the following:1) The equivalence of the experimental and control groups and their validity to start the final experiment.2) There is a statistically significant difference at the level of significance (α = 0.05) between the mean scores of the students of the experimental and control groups in the post-application of the achievement test and in favor of the experimental group whose students studied using the educational platform, and this leads us to reject the first null hypothesis, meaning that there is a positive effect To teach using the educational platform in student achievement.3) There is a positive effect of teaching using the educational platform on students' attitudes towards using the platforms. The research came out with a set of recommendations, including:• The need for the attention of those concerned with education affairs in general, and the curricula and methods of teaching mathematics in particular, by using educational platforms and activating their role in the field of education, through:- Holding training courses for mathematics teachers, before and during service, on the use of educational platforms, and the need to encourage them to use them in their teaching of their subjects.- Developing the mathematics curriculum to include practical applications presented through educational platforms.- Providing advanced computers in computer laboratories, and providing the necessary programs for the educational platform in various disciplines.• The necessity of diversifying and integrating the use of educational platforms with other teaching methods and conducting practical experiments in teaching mathematics.• The research recommends that the mechanisms of education and basic education need to include the method of teaching using educational platforms in teacher preparation programs, so that they can apply it during service effectively.• Conducting more experimental studies on the impact of teaching mathematics using educational platforms at various educational levels, and on other scientific subjects such as physics, chemistry and life sciences.• Conducting more experimental studies that compare the impact of the teaching method on educational platforms and the development of self-learning skills.Keywords: educational platforms, directionAchievement and direction towards it.